2006
DOI: 10.1200/jco.2005.04.3547
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of Cetuximab in Combination With Cisplatin or Carboplatin and Fluorouracil in Patients With Recurrent or Metastatic Squamous Cell Carcinoma of the Head and Neck

Abstract: The combination of cetuximab, cisplatin/carboplatin, and FU was reasonably well tolerated and active in recurrent/metastatic SCCHN, and merits additional investigation. An FU dose of 1,000 mg/m2/d in combination with cisplatin or carboplatin can be recommended for additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 21 publications
3
83
0
1
Order By: Relevance
“…17 The phase I study showed that the addition of cetuximab to a platinum/5-FU combination in the treatment of patients with recurrent and/or metastatic SCCHN was active and well tolerated in the first-line settings. 18 Cetuximab was also effective in nasopharyngeal carcinoma: the combination of cetuximab plus carboplatin showed an important clinical benefit in the patients with recurrent and/or metastatic nasopharyngeal carcinoma failing chemotherapy with an overall response rate of 12% and median overall survival of 7.6 months. 19 …”
Section: Squamous Cell Carcinoma Of the Head And Neck (Scchn)mentioning
confidence: 99%
“…17 The phase I study showed that the addition of cetuximab to a platinum/5-FU combination in the treatment of patients with recurrent and/or metastatic SCCHN was active and well tolerated in the first-line settings. 18 Cetuximab was also effective in nasopharyngeal carcinoma: the combination of cetuximab plus carboplatin showed an important clinical benefit in the patients with recurrent and/or metastatic nasopharyngeal carcinoma failing chemotherapy with an overall response rate of 12% and median overall survival of 7.6 months. 19 …”
Section: Squamous Cell Carcinoma Of the Head And Neck (Scchn)mentioning
confidence: 99%
“…24,25 When initial platinum-based therapy has failed, encouraging results have been reported in patients with recurrent and/or metastatic SCCHN for cetuximab both as monotherapy 26,27 and in combination with either cisplatin or carboplatin. [28][29][30][31] The objective of the analysis reported here was to determine more precisely the scope of cetuximab activity in recurrent and/or metastatic SCCHN in patients who progressed on platinum-based therapy by comparing the intention-to-treat efficacy data from 3 Phase II cetuximab studies with a retrospective study of a similar group of patients who were receiving various types of treatment outside an investigational setting.…”
mentioning
confidence: 99%
“…Three studies were excluded from the analysis: one study used an egfri in both arms 13 , one did not present rash rates according to either grades 3 and 4 criteria or allgrades criteria 14 , and one study was a duplicate of another study 15 . Thus thirteen studies were eligible for inclusion in the meta-analysis ( Table ii).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study provided a rate of discontinuation because of rash (4%) 26 ; others reported discontinuations related to egfri reactions-for example, infusion-related or general toxicity 13,17,23 . Consequently, a systemic review of discontinuation rates could not be conducted, and the pooled difference in rates of discontinuation because of rash a Defined as the presence of one or more incidents of rash or desquamation, dry skin, nail changes, or other skin toxicity of all grades according to the National Cancer Institute's Common Toxicity Criteria, version 2.0. b Defined as any event described as rash, rash pustular, rash erythematous, dermatitis acneiform, dermatitis exfoliative, rash papular, rash pruritic, rash generalized, rash macular, rash maculopapular, acne, dry skin, acne pustular, and skin desquamation.…”
Section: Discussionmentioning
confidence: 99%